2020
DOI: 10.1101/2020.05.15.096719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IgA MAb blocks SARS-CoV-2 Spike-ACE2 interaction providing mucosal immunity

Abstract: SummaryCOVID-19 caused by SARS-CoV-2 has become a global pandemic requiring the development of interventions for the prevention or treatment to curtail mortality and morbidity. No vaccine to boost mucosal immunity or as a therapeutic has yet been developed to SARS-CoV-2. In this study we discover and characterize a cross-reactive human IgA monoclonal antibody, MAb362. MAb362 binds to both SARS-CoV and SARS-CoV-2 spike proteins and competitively blocks hACE2 receptor binding, by completely overlapping the hACE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…In agreement with previous studies, there was a skewing of the repertoire in the response to SARS-CoV-2 infection, with an increased use of certain V genes, an increase in the proportion of antibodies with longer CDRH3s, and an altered isotype subclass distribution 14 . The significantly increased usage of IGHA1 observed in the COVID-19 patients is in line with mucosal responses, where the longer hinge in IGHA1 compared to IGHA2 may offer advantages in antigen recognition by allowing higher avidity bivalent interactions with distantly spaced antigens 25 .…”
Section: Discussionmentioning
confidence: 52%
“…In agreement with previous studies, there was a skewing of the repertoire in the response to SARS-CoV-2 infection, with an increased use of certain V genes, an increase in the proportion of antibodies with longer CDRH3s, and an altered isotype subclass distribution 14 . The significantly increased usage of IGHA1 observed in the COVID-19 patients is in line with mucosal responses, where the longer hinge in IGHA1 compared to IGHA2 may offer advantages in antigen recognition by allowing higher avidity bivalent interactions with distantly spaced antigens 25 .…”
Section: Discussionmentioning
confidence: 52%
“…Since milks of cow and goat contain much lower concentration (0.02-0.2mg/mL) of LF than human breastmilk (1-7mg/ml), the findings that milks of cow and goat inhibited the infectivity of SARS-CoV-2 also suggest that LF is not the active component to inactivate SARS-CoV-2 (21). Besides LF, specific immunoglobulins are also important for the host defense system (18). It was reported that IgA antibody from the recovery patients blocks the interaction of SARS-CoV-2 and ACE2 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Besides LF, specific immunoglobulins are also important for the host defense system (18). It was reported that IgA antibody from the recovery patients blocks the interaction of SARS-CoV-2 and ACE2 (18). As the human breastmilk samples were collected before the emergence of COVID-19, the breastmilk donors should have not been infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 In this respect, several SARS-CoV-2 antibodies targeting the S protein have been identified (Table S11). 61,62,[64][65][66][67][68][75][76][77][78][79] The majority of these antibodies recognizes epitopes on the RBD, while only a few have been shown to address other antigenic regions within the NTD and CD ( Figure S12). Among the RBD antibodies, B38 interacts with the RBM at the RBD/ACE2 interface, 64 whereas S309 and CR3022 target the side/bottom part of the RBD.…”
Section: Glycan Shield Of the Receptor Binding Domainmentioning
confidence: 99%